First contribution to the genus Gymnopilus (Agaricales, Strophariaceae) in Paraguay - Campi, Michelle (2021)
Fil: Campi, Michelle. Universidad Nacional de Asunción. Facultad de Ciencias Exactas y Naturales; Paraguay.